Corporate Governance Between Shareholder and Stakeholder Orientation: Lessons From Germany. (April 2017) - Bottenberg, Konstantin; Tuschke, Anja; Flickinger, Miriam
It is highly debated whether corporations should primarily follow a shareholder or a stakeholder principle. This article addresses the debate with a closer look at Germany's current conceptualization of corporate governance. Despite the introduction of shareholder-oriented practices such as moderate amounts of stock-option pay and more transparent accounting standards, the German corporate governance system is considered to be a prototype of stakeholder orientation. Critics of this system claim that strong obligations to stakeholder interests are a drawback for German firms when competing internationally. However, if applied thoughtfully, an institutionally anchored stakeholder management can also have a number of advantages. We point to selected advantages of a stakeholder-oriented system, including the active integration of stakeholder knowledge, increased commitment for strategic decisions, and a longer term view on performance. Acknowledging potential problems arising from a stakeholder orientation as well as its unique benefits, we call for a "modern" stakeholder value system.